On emotion specificity in decision making - Marcel Zeelenberg; Rob M. A. Nelissen; Seger M. Breugelmans; Rik Pieters (Judgment and Decision Making, 2008)
We present a motivational account of the impact of emotion on decision making, termed the feeling-is-for-doing approach. We first describe the psychology of emotion and argue for a need to be specific when studying emotion's impact on decision making. Next we describe what our approach entails and how it relates emotion, via motivation to behavior. Then we offer two illustrations of our own research that provide support for two important elements in our reasoning. We end with specifying four criteria that we consider to be important when studying how feeling guides our everyday doing.